Mecanismos moleculares da Polioencefalomalácia induzida por Piritiamina - Medeiros, Rita de Cássia Noronha (2020)
Thiamine deficiency results in biochemical and metabolic dysfunctions that affect various regions of the brain, originating cognitive and motor impairments. Thiamin, vitamin B1, is an essential nutrient for nerve tissue. When phosphorylated, it gives rise to different forms, such as thiamine pyrophosphate, which acts as a key enzyme cofactor in cellular energy metabolism. Beriberi, Wernicke encephalopathy (EW) and Wernicke-Korsacoff syndrome (SWK) are the major deficiency diseases in humans. The initial lesions of EW are bleeding into the gray matter around the third and fourth ventricles and the Sylvius aqueduct. Central nervous system (CNS) regions involved in polyencephalomalacia (PEM) are varied and contradictory, but are affected from cortical areas to deep regions such as the midbrain and thalamus. At these sites, there is typically degeneration and neuronal necrosis, with adjacent involvement of astrocytic and inflammatory changes. Little is known about the molecular and cellular mechanisms of degeneration and death of neurons, however, it is considered that the process related to thiamine deficiency is initiated by metabolic defects in the mitochondria, with consequent establishment of oxidative stress. In this work we aimed to determine different parameters related to thiamine deficiency in the CNS in an in vivo model, in order to evaluate the association of lesions and behavioral changes in the model animals and the design of efficient neuroprotective strategies. The dietary deficiency model in combination with thiamine antagonist injections, pyriamine, was used in the study. The animals were treated for 9 days, divided into 6 treatment groups: control (Cont), pyrylamine (Ptd), pyrylamine and trolox (Ptd + Tr), pyritiamine and dimethylsulfoxide (Ptd + Dmso), Trolox (Tr) and Dimethylsulfoxide Dmso). Mice subjected to the thiamine deficiency model (Ptd group) exhibited a significant reduction in body weight gain and feed intake after 9 days of treatment. Thiamine deficient animals presented behavioral alterations such as reduction in motor coordination and exploratory activity. Trolox and Dmso attenuated these effects. In the Ptd group there was a decrease in cell viability in important areas, such as cerebral cortex, hippocampus and thalamus. However, histopathology showed lesions in the thalamus and brain stem, such as hemorrhage, astrocytic vacuolization and spongiosis. In the groups Ptd + Trt and Ptd + Dmso there was a marked attenuation of these lesions. In the western blot evaluations, the Ptd group showed increased phosphorylation of p38MAPK in the cerebral cortex and thalamus. The Ptd + Tr group totally blocked this effect in both encephalic structures. And the group (Ptd + Dmso) reduced the increase in p38MAPK phosphorylation, but less intensely than Trolox. There was an increase in the expression of HO-1 in the Ptd group, already in the Ptd + Trt and Ptd + Dmso groups. No change occurred in the induction of increase in HO-1 expression. These data suggest that in the thiamine deficiency model with pyriamine, animals develop neurological and metabolic changes, possibly associated with oxidative stress and inflammation.